Potential autotrophic carbon-fixer and Fe(II)-oxidizer Alcanivorax sp. MM125-6 isolated from Wocan hydrothermal field - Wei, Mingcong; Zeng, Xiang; Han, Xiqiu; Shao, Zongze; Xie, Qian; Dong, Chuanqi; Wang, Yejian; Qiu, Zhongyan (Frontiers in Microbiology, 2022)
The genus Alcanivorax is common in various marine environments, including in hydrothermal fields. They were previously recognized as obligate hydrocarbonoclastic bacteria, whereas their potential for autotrophic carbon fixation had not been recognized and Fe(II)-oxidation remains largely elusive. In this study, an in-situ enrichment experiment was performed using a hydrothermal massive sulfide slab deployed 300 m away from the Wocan hydrothermal vent. Further, the biofilms on the surface of the slab were used as an inoculum with hydrothermal massive sulfide powder from the same vent as an energy source to enrich the potential iron- oxidizer in the lab. Three dominant bacterial families, Alcanivoraceae, Pseudomonadaceae and Rhizobiaceae, were enriched in the medium with hydrothermal massive sulfides. Subsequently, strain Alcanivorax sp. MM125_6 was isolated from the enrichment culture, which belongs to the genus Alcanivorax and was closely related to Alcanivorax profundimaris ST75FaO-1T (98.90% sequence similarity) indicated by phylogenetic analysis based on the 16S rRNA gene sequences. Autotrophic growth experiments of strain MM125-6 revealed that the cell concentrations increased from an initial 7.5 × 105 cells/ml to 3.13 × 108 cells/ml after 10 days, and δ13CVPDB in the cell biomass also increased from 234.25 ‰ on day 2 to gradually 345.66 ‰ at day 10. Gradient tube incubation showed that the bands of iron oxides and cells formed approximately 1.0 cm and 1.5 cm below the air-agarose medium interface, respectively. In addition, SEM-EDS data demonstrated that it can also secrete acidic exopolysaccharides and adhere to the surface of sulfide minerals to oxidize the Fe(II) with NaHCO3 as the sole carbon source, which accelerates hydrothermal massive sulfide dissolution. These results support the conclusion that strain MM125-6 capable of autotrophic carbon fixation and Fe(II)-oxidization chemoautotrophically. This study expands our understanding of the metabolic versatility of the Alcanivorax genus. This also indicates that the genus Alcanivorax might play an important role(s) in coupling hydrothermal massive sulfide weathering and iron and carbon cycles in hydrothermal fields.